Discrediting in a message board forum: The effects of social support and attacks on expertise and trustworthiness - Hughes, M.; Griffith, J.; Zeni, T.; Arsenault, M.; Cooper, O.; Johnson, Genevieve; Hardy, J.; Connelly, S.; Mumford, M. (2014)
Given the prevalence of online media today, credibility continues to be a popular subject of empirical research. However, studies examining the effects of discrediting strategies are rare. This issue is significant given the popularity of online media and the ease of such sources to spread misinformation. Therefore, the present study examines the effects of attacking the expertise and trustworthiness of a proponent of a major social issue. Results showed that support as well specific combinations of discrediting attack strategies significantly reduced message board readers' perceptions of the proponent's credibility. In addition, attacks on either the proponent's expertise or trustworthiness resulted in a reduced likelihood of readers taking action with respect to the issue.